PENDEKATAN KUALITATIF PADA EVALUASI EFEKTIVITAS PROGRAM - Safaria, Anne Friday (LPPM UNSAP & FISIP UNSAP, 2025)
This research synthesizes academic literature on measuring the effectiveness of policies and programs, primarily focusing on challenging the dominance of the quantitative (goal-oriented) approach. This traditional method often fails to capture the essential dynamics within complex adaptive systems. The key research question guiding this study is: How can qualitative frameworks, criteria, and dimensions be utilized to assess program success holistically? The study employs an Academic Literature Synthesis to construct a set of credible theoretical frameworks that support the validity and legitimacy of non-quantitative effectiveness measurement. This involves critically analyzing literature that critiques conventional quantitative metrics and discusses the development of qualitative models such as Utilization-Focused Evaluation (U-FE) and Principles-Focused Evaluation (P-FE). The synthesis confirms a necessary paradigm shift, where effectiveness is primarily characterized by Internal Learning (Process Use), Actual Utilization, and Contextual Adaptation. Core qualitative dimensions identified include changes in attitudes/capacity, building trust, and program adaptation to local needs. These findings validate the qualitative approach as a structured and essential evaluation paradigm for complex programs. The main contribution to Public Administration is providing a strong theoretical foundation for practitioners to move beyond relying solely on quantitative figures